Electroresponsive Structurally Colored Materials: A Combination of Structural and Electrochromic Effects. (12th January 2016) - Kuno, Tomoya; Matsumura, Yoshimasa; Nakabayashi, Koji; Atobe, Mahito
Abstract: Electroresponsive structurally colored materials composed of ordered arrays of polyaniline@poly(methyl methacrylate) (PANI@PMMA) core–shell nanoparticles have been successfully prepared. The core–shell nanoparticles were synthesized by deposition of PANI shells on the surfaces of the PMMA cores by the oxidative polymerization of anilinium chloride. Ordered arrays were then fabricated by using the fluidic cell method. Because the ordered arrays and the PANI shells generate structural and electrochromic colors, respectively, these core–shell colloidal crystals exhibited colors resulting from the combined effects of these materials. The crystal colors depended greatly on the size of PANI@PMMA particles and could also be varied by the application of a voltage. The electrochromic colors of these arrays were found to be quite different from those exhibited by pure PANI films prepared by electrochemical oxidation.